Vegetación gipsícola del sector antequerano (provincia bética, Andalucía). Vegetation on gypsum soils of the Antequerano biogeographical sector (Betica province, Andalusia) - Cabezudo, Baltasar; Pérez Latorre, Andrés V.; Casimiro-Soriguer Solana, Federico (Acta Botanica Malacitana, 2013)
Vegetation on gypsum soils of the Antequerano biogeographical sector (Betica province, Andalusia) Palabras clave. Vegetación, flora, gipsófito, gipsófilo, Andalucía, España. Key words. Vegetation, flora, gypsophyte, gysophile, Andalusia, Spain.